New record of the genus Mylodiscus Thorne, 1939 (Dorylaimida, Qudsianematidae) for Vietnam fauna with redescription of Mylodiscus nanus Thorne, 1939 - Thanh Tam, Vu Thi (Academia Journal of Biology, 2016)
Mylodiscus nanus Thorne, 1939 of the genus Mylodiscus Thorne, 1939 e was recorded for the first time in Vietnam. Two populations of this species were collected from Bach Ma National Park (Thua Thien-Hue province) and Cham Chu NatureReserve (Tuyen Quang province). All measurements and illustrations fitted well with other populations from different localities in the world. Based on the specimens of M. nanus collected from Vietnam, the rescription of this species was also given.